A High-Efficiency Ultra-Broadband Mixed-Mode GaN HEMT Power Amplifier - Krishnamoorthy, Ragavan; Kumar, Narendra; Grebennikov, Andrei; Ramiah, Harikrishnan (Institute of Electrical and Electronics Engineers, 2018)
In this brief, a new technique of efficiency enhancement of ultra-broadband RF power amplifier with simple load network approach is introduced, in which a combination of the reactance compensation and third-harmonic tuning is developed with design equations. The fabricated prototype board of the mixed mode power amplifier demonstrated 10 W output power over a wide frequency band of 0.4-2.0 GHz with an efficiency greater than 62% and observes good agreement between simulation and measured output. This implementation is suitable for two-way radio product applications.